Measurement of ship-generated waves in German coastal waterways from 1998–2022 - Arne Seemann; Gregor Melling (Scientific Data)
Abstract Vessel-generated waves and currents significantly impact coastal and estuarine waterways. In-situ measurements record all relevant physical phenomena that occur under a wide range of conditions and are therefore a valuable resource in the investigation of ship waves. Here we present a comprehensive compound dataset from in-situ ship wave measurement campaigns conducted over several decades in German coastal waterways. The dataset includes measured ship waves heights and currents as well as an attribution of each wave event to ship and nautical parameters responsible for its generation. The dataset is unique in its scope, combining a significant number of data points from multiple sites with different cross-section profiles. Some campaigns feature multiple gauges per cross-section, facilitating the analysis of wave transformation processes. Some locations feature repeat measurements which helps to understand wave load histories due to e.g. changes in shipping fleet structures and navigation practices. This dataset aims to provide a basis to enhance data-driven models to predict and manage the impacts of vessel-generated waves in different topographic settings and fleet structures.